2017
DOI: 10.1039/c7ra10920b
|View full text |Cite
|
Sign up to set email alerts
|

Protein droplet actuation on superhydrophobic surfaces: a new approach toward anti-biofouling electrowetting systems

Abstract: Anti-biofouling behaviour of an electrowetting device using off-the-shelf superhydrophobic materials is demonstrated through protein adsorption measurement and protein-laden droplet actuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…First, since deposition of a defect-free thin film is challenging, especially across the relatively large area of some devices, the dielectric layer often experiences electric leakage or even breakdown 14 , resulting in the notorious device failure by electrolysis 24 . Second, this hydrophobic topcoat, for example, polytetrafluoroethylene (PTFE), is susceptible to dielectric charging 15,40 and prone to protein fouling 16 , not to mention its material and deposition costs. Despite the associated problems, the dielectric layer and hydrophobic topcoat (enabling EWOD) were the critical advances that made the once-obscure concept of electrowetting practical in applications, leading to the digital microfluidics of today.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, since deposition of a defect-free thin film is challenging, especially across the relatively large area of some devices, the dielectric layer often experiences electric leakage or even breakdown 14 , resulting in the notorious device failure by electrolysis 24 . Second, this hydrophobic topcoat, for example, polytetrafluoroethylene (PTFE), is susceptible to dielectric charging 15,40 and prone to protein fouling 16 , not to mention its material and deposition costs. Despite the associated problems, the dielectric layer and hydrophobic topcoat (enabling EWOD) were the critical advances that made the once-obscure concept of electrowetting practical in applications, leading to the digital microfluidics of today.…”
Section: Methodsmentioning
confidence: 99%
“…Such electrical actuation is mainly achieved by electrowetting, with droplets attracted towards and spreading on a conductive substrate in response to an applied voltage. To ensure strong and practical actuation, the substrate is covered with a dielectric layer and a hydrophobic topcoat for electrowetting-on-dielectric (EWOD) 11-13 ; this increases the actuation voltage (to about 100 volts) and can compromise reliability owing to dielectric breakdown 14 , electric charging 15 and biofouling 16 . Here we demonstrate droplet manipulation that uses electrical signals to induce the liquid to dewet, rather than wet, a hydrophilic conductive substrate without the need for added layers.…”
mentioning
confidence: 99%
“…Whilst, an increase of the voltage directly increases the actuation force, hence facilitating magnetic extraction, it also participates in increasing the biofouling rate (Latip et al 2017;Yoon and Garrell 2003). Accordingly, based on a series of preliminary experiments described in appendix B (available online as supplementary material), 105 V rms was selected as the operating voltage for the DMF assay with a couple of exceptions: firstly, the minimal reliable actuation for the luminol:H 2 O 2 droplet was found to be 120 V rms and secondly, a higher voltage of 165 V rms was used to produce a higher force during the magnetic separation process.…”
Section: Resultsmentioning
confidence: 99%
“…A larger 5 x 5 mm 2 pad is used as waste pad for separated supernatant. The EWOD chip operates using the common parallel-plate configuration ( Figure 2c) (Latip et al 2017). In this configuration, the droplet is sandwiched between the hydrophobic surfaces of the actuation plate and a conductive, grounded cover plate both separated by a precisely defined gap.…”
Section: The Design and Fabrication Of The Ewod Chipmentioning
confidence: 99%
“…Biofouling is the main limitation of EWOD for biological applications 22,23 . Earlier studies on DMF have identified two mechanisms that contribute to biofouling, namely, passive adsorption due to hydrophobic interactions, and an electrostatically driven adsorption manifesting when an electric field is applied 24 .…”
mentioning
confidence: 99%